Hubungan Asupan Vitamin E dengan Kejadian Dismenore pada Remaja Putri di SMA Negeri Kecamatan Tuban - Lailia Rohmatun Nazila; Lilia Faridatul Fauziah (Yayasan Literasi Sains Indonesia, 2024)
Dysmenorrhea is abdominal pain that comes from uterine cramps and occurs before, during or after menstruation. There are several factors that can affect the incidence of dysmenorrhea, one of which is nutrient intake. The purpose of this study was to determinate the relationship between vitamin E intake and the incidence of dysmenorrhea in female adolescents at SMA Negeri Tuban District. This type of research is a quantitative study with a correlation design using a cross-sectional approach. The sampel of this study was adolescent girl at SMA Negeri Tuban District as many as 199 respondents selected using the cluster random sampling techniques. The analysis of this study used the spearman correlation statistical test. The results of the study showed that adolescent girl with severe vitamin E deficit intake experienced moderate pain with a percentage of 40,0%. The result of the statistical test showed that there was a significant relationship between vitamin E intake and the incidence of dysmenorrhea (p-value = 0,004). Based on the results of the study, it can be concluded that one of the nutrients that can affect the incidence of dysmenorrhea in adolescents girl is vitamin E. The lower the intake vitamin E, the more at risk adolescent girl are of experiencing dysmenorrhea. It is hoped that adolescent girl can implement a balanced diet to reduce dysmenorrhea pain.